Respuesta :

Answer: Third Choice. 9

Step-by-step explanation:

Concept:

Here, we need to understand the idea of evaluation.    

When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.

Solve:

Given

4x + 2y -1

x = 3, y = -1

Substitute the value of x and y

4(3) + 2(-1) - 1

Simplify by multiplication

12 - 2 - 1

Simplify by subtraction

9

Hope this helps!! :)

Please let me know if you have any questions

Answer:

Step-by-step explanation:

Hello!

4x= 4*3 = 12

2y = 2*-1 = -2

12-2  -1= 9